3x=4x-((4*x)*.0285)

Simple and best practice solution for 3x=4x-((4*x)*.0285) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x=4x-((4*x)*.0285) equation:


Simplifying
3x = 4x + -1((4x) * 0.0285)

Remove parenthesis around (4x)
3x = 4x + -1(4x * 0.0285)

Reorder the terms for easier multiplication:
3x = 4x + -1(4 * 0.0285x)

Multiply 4 * 0.0285
3x = 4x + -1(0.114x)

Remove parenthesis around (0.114x)
3x = 4x + -1 * 0.114x

Multiply -1 * 0.114
3x = 4x + -0.114x

Combine like terms: 4x + -0.114x = 3.886x
3x = 3.886x

Solving
3x = 3.886x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3.886x' to each side of the equation.
3x + -3.886x = 3.886x + -3.886x

Combine like terms: 3x + -3.886x = -0.886x
-0.886x = 3.886x + -3.886x

Combine like terms: 3.886x + -3.886x = 0.000
-0.886x = 0.000

Divide each side by '-0.886'.
x = 0

Simplifying
x = 0

See similar equations:

| (-2/7)x(-7/9) | | 16(B+4)=64 | | -6(1+3n)=174 | | 13x+17y=3301 | | 2x-8(2-6x)= | | 10-3x=2(5-x) | | 10X-2X=9+3 | | 9/(3.6-2.1) | | 8-2x=-20+5x | | 6y-2=3y+14-x | | 9x-84=9x-60 | | 3(A-6)=0 | | 14-3(6x-7)=2x+10-35 | | 3x=4x-(4x*0.285) | | 20+3x=36-x | | 6-6(x+2)=10+2x | | 60+3x=12-x | | 12x-7=-17 | | 20+3x=12-x | | (3xy^2)/(21x^4yz^-4) | | 3(5+6)-4(4)=2(4)-16+5(a+1) | | x/1-1/x=8/3 | | 23-3*6/9 | | 7x-2=10x-8 | | -12=-144 | | (3a-2)-(3-5a)=1 | | 7/5p-10=30 | | 8x=296 | | -6+x=-8(1-7x)+2 | | (-5x^3+2x^2-x+5)-(-5x^3+3x^2+5x+3)= | | -3.3+-9.1= | | (x+6)8=-24 |

Equations solver categories